HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG GIZI BALITA DENGAN STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS GAJAH 1 DEMAK - Endang Susilowati; Alin Himawati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Nutritional status is one indicator of health is considered successful achievements in MDGs (Millennium Development Goals). Nutritional status is important because one of the risk factors for morbidity and mortality. Nutritional status is good for one will contribute to health. Knowledge of nutrition toddler is a factor that can affect the nutritional status of children because mother with good knowledge will apply knowledge of nutritional behavior through the provision of nutritious food for toddlers. The purpose of this study was to determine the relationship between the mother's level of knowledge about nutrition with nutritional status of children under five in the area of Occupational Health Center Gajah 1 Demak.Type of observational analytic survey research with cross-sectional time approaches, the number of samples of 95 respondents with sampling stratified random sampling technique. Test the relationship between variables using Chi-Square.The results showed that the majority Good level of knowledge of the majority of respondents were 53 respondents (55%) have nourished toddlers that is 81.13% more than those with less knowledge is 54.76%. The majority of children under five suffering malnutrition and poor have bad knowledgeable mothers were 19 respondents (45.23%). Of statistical test P = 0.006, which means at p 0.05.Conclusion, there is a meaningful relationship between the level of knowledge mother toddler nutrition toddler. Advice for moms toddlers to increase knowledge about nutrition toddler.